2018
DOI: 10.4196/kjpp.2018.22.6.671
|View full text |Cite
|
Sign up to set email alerts
|

Tussilagone suppressed the production and gene expression of MUC5AC mucin via regulating nuclear factor-kappa B signaling pathway in airway epithelial cells

Abstract: In the present study, we investigated whether tussilagone, a natural product derived from Tussilago farfara, significantly affects the production and gene expression of airway MUC5AC mucin. Confluent NCI-H292 cells were pretreated with tussilagone for 30 min and then stimulated with EGF (epidermal growth factor) or PMA (phorbol 12-myristate 13-acetate) for 24 h or the indicated periods. The MUC5AC mucin gene expression was measured by RT-PCR. Production of MUC5AC mucin protein was measured by ELISA. To elucida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…Comparatively, most previous studies have suggested that TUS suppresses the activation of NF-kB pathway, while the modulated targets vary. Cheon et al (2018), Choi et al (2018), Hwang et al (2018), Kim et al (2017b), Lee et al (2016) and Lim et al (2008) all have reported that TUS blocks NF-kB pathway in exogenous-agent-induced colitis mice, airway epithelial cells, focal cerebral ischemia rats, septic mice, skin inflammation mice, and BV-2 microglial cells by attenuating the nuclear translocation of p65 subunit and the phosphorylation and (or) degradation of IkBa. Among them, Choi et al (2018) have also observed the alleviation of phosphorylated IKK complex.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Comparatively, most previous studies have suggested that TUS suppresses the activation of NF-kB pathway, while the modulated targets vary. Cheon et al (2018), Choi et al (2018), Hwang et al (2018), Kim et al (2017b), Lee et al (2016) and Lim et al (2008) all have reported that TUS blocks NF-kB pathway in exogenous-agent-induced colitis mice, airway epithelial cells, focal cerebral ischemia rats, septic mice, skin inflammation mice, and BV-2 microglial cells by attenuating the nuclear translocation of p65 subunit and the phosphorylation and (or) degradation of IkBa. Among them, Choi et al (2018) have also observed the alleviation of phosphorylated IKK complex.…”
Section: Discussionmentioning
confidence: 96%
“…TUS, the main component of T. farfara, was described to have anti-platelet-aggregation and cardiovascular-respiratory stimulating effects in previous studies (Hwang et al, 1987;Li and Wang, 1988). In recent years, several studies have proven beneficial in the treatment of diseases such as diabetic obesity (Park et al, 2008), cancers , and various inflammatory diseases (Lee et al, 2016;Kim et al, 2017b;Cheon et al, 2018;Choi et al, 2018;Hwang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tussilagone (TUS) is a type of sesquiterpenoids that was isolated from the flower of Tussilago Farfara or some other species in the genus Tussilago. Previous studies suggested that this natural compound exerts therapeutical effects in inflammatory pulmonary diseases [16], inflammatory intestinal diseases (IBD) [17], ischemic stroke [18], colon cancer [19], obesity and type 2 diabetes [20], demonstrating multiple regulatory characteristics in diverse pathophysiological changes like antiinflammation [21][22][23], anti-oxidation [24,25], anti-tumor [19]. Especially, TUS was found attenuating lipopolysaccharide (LPS)-induced inflammatory mediators production in RAW264.7 cell via NF-κB and (or) MAPK signaling cascades in several studies [21][22][23], therefore may falling in the candidates of possible drugs to protect bone by suppressing osteoclast formation and activation.…”
Section: Introductionmentioning
confidence: 99%